Mikroregiony pohledem obcí - Sobotka, Martin (Univerzita Pardubice, 2006)
This article deals with microregions and problems linked with. At the beginning microregion is characterized from the legal point of view as well as its possible activities. The article is based on question inquiry in municipalities, which is focused on the main microregion's activities and evaluating of microregion's benefits and lacks, because in general microregions are declared to be highly useful.
Keywords: mikroregiony; obce; svazky obcí; Regionální rozvoj